2011
DOI: 10.2108/zsj.28.206
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Dependent Changes in Bioconvection ofTetrahymenaandChlamydomonasDuring Parabolic Flight: Increases in Wave Number Induced by Pre- and Post-Parabola Hypergravity

Abstract: Bioconvection emerges in a dense suspension of swimming protists as a consequence of their negative-gravitactic upward migration and later settling as a blob of density greater than that of water. Thus, gravity is an important parameter governing bioconvective pattern formation. However, inconsistencies are found in previous studies dealing with the response of bioconvection patterns to increased gravity acceleration (hypergravity); the wave number of the patterns has been reported to decrease during the hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…It also showed that the 'bottle-shaped' settling blobs are formed in SS1 (Fig. 6A, 5 min), as reported previously (Hosoya et al, 2010;Kage et al, 2011). At the moment the pattern transition response occurred (Fig.…”
Section: Two-axis Viewsupporting
confidence: 87%
See 4 more Smart Citations
“…It also showed that the 'bottle-shaped' settling blobs are formed in SS1 (Fig. 6A, 5 min), as reported previously (Hosoya et al, 2010;Kage et al, 2011). At the moment the pattern transition response occurred (Fig.…”
Section: Two-axis Viewsupporting
confidence: 87%
“…Vertical observation (Fig. 6A, left column) showed that the onset of pattern formation occurs after the accumulation of the cells at the top of the chamber (0-2 min), as reported in previous studies (Hosoya et al, 2010;Kage et al, 2011). It also showed that the 'bottle-shaped' settling blobs are formed in SS1 (Fig.…”
Section: Two-axis Viewsupporting
confidence: 84%
See 3 more Smart Citations